Pengaruh Sultan Agung dalam Perpolitikan Jawa - Nurul Lailia; Dwi Susanto; Muhammad Khodafi (Department of History and Islamic Civilization, Faculty of Adab and Humaniora, UIN Sunan Ampel Surabaya, 2022)
Abstract: The third ruler of the Mataram Kingdom who led Mataram to its pinnacle of splendor was Sultan Agung. His use of politics to expand his territory over several Javanese provinces, including East Java, was one of his achievements. This study aims to: (1) ascertain the state of the Islamic Mataram Kingdom during Sultan Agung's rule. (2) Describe the expansion politics that Sultan Agung pursued in the eastern part of Java; (3) Examine Sultan Agung's approach to implementing the expansion policy in the eastern part of Java. A literature review gathers data sources for this study using qualitative research methodologies. The outcomes are as follows: (1) Sultan Agung's leadership has enabled Mataram to grow quickly to become the biggest empire in the Javanese archipelago between 1614 and 1645. This demonstrates how Sultan Agung elevated Mataram to the top in several domains, including politics, economics, religion, and territorial expansion (2) As a political pretext for his conquest, Sultan Agung began his first military campaign against eastern Java in 1614. Afterwards, between 1615 and 1625, Sultan Agung was able to subjugate regions of East Java, including Wirasaba, Siwalan and Lasem, Pasuruan, Tuban, and Surabaya. (3) Understanding the road, the weather and seasons, controlling the terrain, granting orders, and maintaining discipline by the war leader's standards were all part of the expansion strategy to East Java. Keywords: Political Influence, Sultan Agung, Java